Breast cancer and funnel chest: comparing helical tomotherapy and three-dimensional conformal radiotherapy with regard to the shape of pectus excavatum - Uhl, Matthias; Sterzing, Florian; Habl, Gregor; Schubert, Kai; Hof, Holger; Debus, Jürgen; Herfarth, Klaus (Strahlentherapie und Onkologie, 2012)
Background and purpose: Preserving lung, heart, and the contralateral breast from toxicity is a technical challenge in women with funnel chest, who require breast irradiation. The purpose of this study was to determine whether helical tomotherapy (HT) offers an advantage compared to three-dimensional (3D) conformal radiotherapy (CRT) for patients with pectus excavatum with regard to its shape. Patients and methods: Ten breast cancer patients with pectus excavatum were graded into a low or high deformation group using different indices, measured and calculated by using the planning CT. A planning comparison was performed, creating plans for CRT and HT. Target uniformity, target conformity, and exposure to the organs at risk (OARs) were compared. Results: The uniformity and conformity of the target dose distribution and the median/average dose of the planning target volume (PTV) was inferior in CRT compared to HT in both deformation groups. By using tomotherapy, the volume of the lungs, the contralateral breast, and the heart, which received high dose exposure, could be significantly reduced. Tomotherapy plans led to a significantly higher low dose exposure to the lungs and contralateral breast. Conclusion: This is the first study which evaluates a group of 10 breast cancer patients with funnel chest. Better uniformity and conformity combined with a significant reduction of high dose exposure to the OARs can be reached using tomotherapy. However, tomotherapy plans have a significantly larger volume of low dose to the lungs and contralateral breast. Therefore, the stochastic risk should be considered after low dose exposure in women with low deformation.